Recurrence of Primary Vascular Leiomyosarcoma Five Years after Initial Diagnosis in the Lower Extremity - Hilal Erinanc; Mehmet Ozulku; Aysen Terzi (Case Reports in Oncological Medicine)
Primary leiomyosarcomas of vascular origin are rare tumors. They frequently arise within the inferior vena cava; however, the peripheral vein was also affected. To date, only a few hundred cases have been reported in the world literature. Although it is an extremely aggressive tumor, the symptoms may be unspecific, especially in the lower extremities. In this report, we present a case of primary vascular leiomyosarcoma, arising from the short saphenous vein, with symptoms mimicking thrombus in the initial diagnosis. The diagnosis of leiomyosarcomas was confirmed by standard H&E staining and immunohistochemical staining. Recurrence of the tumor has been observed five years after surgical treatment. Due to its rarity, experience in the management of this type of tumor is limited. The mainstay of treatment for these tumors is complete surgical resection. The purpose of the presented case is to discuss the clinicopathological features and management options of this tumor, under the light of the most recent literatures.